2017
DOI: 10.1177/2472555217724437
|View full text |Cite
|
Sign up to set email alerts
|

Earthworms as a Biocatalyst: In Asymmetric Aldol Reactions

Abstract: A crude extract from earthworms was used as an environmentally friendly and easily accessible biocatalyst for asymmetric direct aldol reactions. The β-hydroxy carbonyl compounds could be prepared in yields of up to 94%, with ee values of up to 98% and dr of up to >99:1. A wide range of substrates could participate in the reaction. This earthworm catalyst was also efficient in the large-scale reaction, providing product in excellent yield and good selectivity. The protocol as an example gives inspiration for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…This outcome may suggest longer reaction times are required for the formation of the product. The aforementioned solvents were selected in this study because they are readily available in the lab and they have been reported in literature, 3,45 to yield aldol products with high yields and good selectivity. Although high-boiling organic solvents such as DMSO and DMF are commonly used in aldol reactions studies they are oen considered problematic for large-scale synthesis due to inconvenient work-up, solvent removal and recovery steps.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…This outcome may suggest longer reaction times are required for the formation of the product. The aforementioned solvents were selected in this study because they are readily available in the lab and they have been reported in literature, 3,45 to yield aldol products with high yields and good selectivity. Although high-boiling organic solvents such as DMSO and DMF are commonly used in aldol reactions studies they are oen considered problematic for large-scale synthesis due to inconvenient work-up, solvent removal and recovery steps.…”
Section: Peptide Synthesismentioning
confidence: 99%
“…They reported the products yields up to 51% with enantioselectivities up to 87% for the reaction. Zhang et al, (28) used earthworm extract as an environmental biocatalyst for asymmetric synthesis of various β-hydroxy carbonyl compounds in yields up to 94%, ee values of up 98% and dr values of up to 99%.…”
Section: Introductionmentioning
confidence: 99%